Nakhaandeh dar Tehran - Keshavarz, Mina (Iran, 2011)
Inspired by her own choice to marry in order to move to Tehran, the filmmaker decided to make a documentary about Iranian girls, like Azar, who move to the capital in order to start an independent life. The film seeks answers as to why Iranian society has such difficulty accepting independent life for single women.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films